Developing Rainfall-Based Index Insurance in Morocco - Skees, Jerry (World Bank, Washington, DC, 2014)
Cereal production accounts for about seventy percent of all agricultural land in Morocco. Cereal producer prices, influenced by the government, are higher than world prices. Production is divided into six broad agro-climatic zones. About half of cereal production is concentrated in the favorable, and intermediate zones; the rest occurs mostly in less favorable (arid and semi-arid) zones, with average annual rainfall below 450 millimeters. The authors assess the feasibility of rainfall-based index insurance, to provide effective, low-cost drought insurance for Moroccan farmers, and rural dwellers. Their analysis focuses on Morocco's three main cereal crops - hard wheat, soft wheat, and barley - using data on annual production, and planting from 1978-99. Maize is included in some of the analysis. The benefits of this program over the traditional insurance scheme are that it minimizes the risk of moral hazard, and adverse selection, and promotes a streamlined pay-out-process. These features make the program more attractive to international re-insurers, and investors in capital markets. A rainfall-indexed insurance product is feasible in Morocco, where the statistical correlation between rainfall, and cereal revenues is rather strong in seventeen provinces in the more favorable agro-climatic zones. Proportional rainfall insurance contracts, would pay the insured an amount based on the shortfall in actual rainfall, during a set period, compared with the trigger rainfall. The contracts could be purchased in any amount, allowing farmers to insure the full amount of their expected revenue, if they wish.